2014
DOI: 10.1371/journal.pone.0086234
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PP2AC Carboxylmethylation and Cellular Localisation by Inhibitory Class G-Protein Coupled Receptors in Cardiomyocytes

Abstract: The enzymatic activity of the type 2A protein phosphatase (PP2A) holoenzyme, a major serine/threonine phosphatase in the heart, is conferred by its catalytic subunit (PP2AC). PP2AC activity and subcellular localisation can be regulated by reversible carboxylmethylation of its C-terminal leucine309 (leu309) residue. Previous studies have shown that the stimulation of adenosine type 1 receptors (A1.Rs) induces PP2AC carboxylmethylation and altered subcellular distribution in adult rat ventricular myocytes (ARVM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Methylation of PP2A-C can lead to more frequent localization to certain membranes or membrane rafts. Longman, Ranieri, Avkiran, and Snabaitis (2014) reported that stimulation of A1 receptors (a type of G-coupled receptors in mammals) increased the association of LCMT1 with PP2A-C and thereby augmented the carboxymethylation of the C subunits and facilitated association of PP2A-C with membrane-rich particulate compartments. Sontag, Nunbhakdi-Craig, and Sontag (2013) reported coenrichment of LCMT1, methylated PP2A-C, and Bα in cholesterol-rich membrane rafts of mammalian N2a cells.…”
Section: Halfordsmentioning
confidence: 99%
“…Methylation of PP2A-C can lead to more frequent localization to certain membranes or membrane rafts. Longman, Ranieri, Avkiran, and Snabaitis (2014) reported that stimulation of A1 receptors (a type of G-coupled receptors in mammals) increased the association of LCMT1 with PP2A-C and thereby augmented the carboxymethylation of the C subunits and facilitated association of PP2A-C with membrane-rich particulate compartments. Sontag, Nunbhakdi-Craig, and Sontag (2013) reported coenrichment of LCMT1, methylated PP2A-C, and Bα in cholesterol-rich membrane rafts of mammalian N2a cells.…”
Section: Halfordsmentioning
confidence: 99%
“…The constitutively active Pak1, the downstream effectors for Cdc42 and Rac1 induces activation of PP2A and dephosphorylation of myofilament regulatory proteins (Ke et al, 2004 ). PI3K is another possible link between Gi and PP2A activities that enhances carboxylmethylation at leu309 (Longman et al, 2014 ) (Figure 2 ).…”
Section: Pp2a and Its Regulation By Upstream Signals In The Heartmentioning
confidence: 99%
“…Regarding signaling, LCMT-1 methylation of the PP2A C subunit is stimulated by multiple GiPCR agonists in adult rat ventricular myocytes (Ref. 27 and references therein); LCMT-1 is a negative regulator of Akt and p70/p85 S6 kinase (28); and LCMT-1 helps prevent anchorage-independent growth of cells (28).…”
mentioning
confidence: 99%